Assignment of the Gene for Adenine Phosphoribosyltransferase to Human Chromosome 16 by Mouse-Human Somatic Cell Hybridization - Tischfield, Jay A. (1974)
A series of mouse-human hybrids was prepared from mouse cells deficient in adenine phosphoribosyltransferase (EC 2.4.2.7) and normal human cells. The hybrids were made in medium containing adenine and alanosine, an antimetabolite known to inhibit de novo adenylic acid biosynthesis. The mouse cells, unable to utilize exogenous adenine, were killed in this medium, but the hybrids proliferated as a consequence of their retaining the human aprt gene. The hybrids were then exposed to the adenine analogs 2,6-diaminopurine and 2-fluoroadenine to select for cells that had lost this gene. Before exposure to the adenine analogs, the expression of human adenine phosphoribosyltransferase by the hybrids was strongly associated only with the presence of human chromosome 16, and afterwards this was the only human chromosome consistently lost. This observation suggests that the human aprt gene can be assigned to chromosome 16.